Antioxidant Activity of Selected Herzegovinian Wines - Marković, M.; Talić, S. (Kemija u industriji; časopis kemičara i tehnologa Jugoslavije, 2013)
Many wines, particularly red, contain different compounds that possess strong antioxidant activity. The subject of this paper was the determination of phenol compounds with strong antioxidant activity, contained in nine commercially available Herzegovinian red wines. Total phenols, flavonoids, nonflavonoids content and antioxidant activity of selected wines were determined. Total phenols content was determined spectrophotometrically by the Folin-Cioca@lteu method using gallic acid as standard, while flavonoids and nonflavonoids content was determined by using formaldehyde. Two distinct methods were used to assess the antioxidant capacity of the tested wines; Briggs-Rauscher oscillating reaction method, and the reduction of DPPH radicals. Total phenols content in nine studied wines, expressed as Gallic Acid Equivalent (GAE), range from 346.836 mg L-1 to 2169.7 mg L-1, which is consistent with data from previous studies of red wines from other regions. All studied wines showed significantly higher flavonoids content compared to nonflavonoids, an average of 85 : 15. The results indicate significant differences in antioxidant activity of the analyzed wines. According to both applied methods, similar data were measured. A positive and strong correlation between total phenol content and antioxidant activity (by DPPH method, r = 0.93, according to the method of BR oscillating reaction r = 0.90) confirms the fact that wines with higher total phenols content have stronger antioxidant activity.